PENGARUH VARIASI JUMLAH SUDU TERHADAP EFISIENSI PADA PROTOTYPE PEMBANGKIT LISTRIK TENAGA MIKROHIDRO (PLTMH) DENGAN MENGGUNAKAN TURBIN VORTEX - Rekha Agustha, Kadek; Jasa, Lie; Suartika, I Made (Jurnal SPEKTRUM; Vol 9 No 3 (2022): Jurnal SPEKTRUMDO - 10.24843/SPEKTRUM.2022.v09.i03.p4, 2022)
Micro-hydro power plants using vortex turbines have the advantage that their operation can be carried out at low levels of falling water or head. One of the problems that exist in vortex turbine is there is no equation to determine the maximum output generated by the number of blades used. Based on the problems described, a prototype of micro-hydro power plants using vortex was made to test the variations in the number of blades to get the best efficiency. The prototype test in this study used a turbine with various number of blades of 3, 5, and 9 blades. Based on the research conducted, the increase of micro-hydro power plant prototype performance equals to number of blades used. When the system was set with a discharge of 4.5 liters per second paired with a turbine consisted of 9 blades which produced 303.8 rpm of turbine rotation before coupled by the generator and 230.5 rpm after coupled by the generator, the generator rotation was 653.5 rpm, the generator output voltage was 8.29 Volts, generator current output was 0.046, generator power output was 0.387 Watt, torque was 0.0393 Nm, and the highest efficiency was 2.92%